Inborn errors of immunity with susceptibility to S. aureus infections - Kurz, Hannah; Lehmberg, Kai; Farmand, Susan (Frontiers in Pediatrics, 2024)
Staphylococcus aureus (S. aureus) is a significant human pathogen, in particular in patients with an underlying medical condition. It is equipped with a large variety of virulence factors enabling both colonization and invasive disease. The spectrum of manifestation is broad, ranging from superficial skin infections to life-threatening conditions like pneumonia and sepsis. As a major cause of healthcare-associated infections, there is a great need in understanding staphylococcal immunity and defense mechanisms. Patients with inborn errors of immunity (IEI) frequently present with pathological infection susceptibility, however, not all of them are prone to S. aureus infection. Thus, enhanced frequency or severity of S. aureus infections can serve as a clinical indicator of a specific underlying immunological impairment. In addition, the analysis of immunological functions in patients with susceptibility to S. aureus provides a unique opportunity of understanding the complex interplay between staphylococcal virulence and host immune predisposition. While the importance of quantitatively and qualitatively normal neutrophils is widely known, less awareness exists about the role of specific cytokines such as functional interleukin (IL)-6 signaling. This review categorizes well-known IEI in light of their susceptibility to S. aureus and discusses the relevant associated pathomechanisms. Understanding host-pathogen-interactions in S. aureus infections in susceptible individuals can pave the way for more effective management and preventive treatment options. Moreover, these insights might help to identify patients who should be screened for an underlying IEI. Ultimately, enhanced understanding of pathogenesis and immune responses in S. aureus infections may also be of relevance for the general population.